2022
DOI: 10.1002/ece3.9464
|View full text |Cite
|
Sign up to set email alerts
|

Identifying priority reserves favors the sustainable development of wild ungulates and the construction of Sanjiangyuan National Park

Abstract: Sanjiangyuan National Park (SNP), the first national park in China, is one of the most important biodiversity conservation areas in the Sanjiangyuan National Nature Reserve (SNNR) and even the world. The threatened ungulates play an irreplaceable role in maintaining the ecosystem diversity and stability in SNNR. Here, based on 1434 occurrence records of six ungulates, the maximum entropy model, with two different strategies, was utilized to determine the priority reserves. The results indicated that the priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The mean annual temperature in the habitats of the two studied ungulates was below − 1.0°C, indicating a strong correlation with suitable habitats at higher altitudes. Studies within the Sanjiangyuan National Park have shown that the habitats of six ungulate species are typically above 4,300 meters, where the mean annual temperature falls below − 3.0°C 19 . The mean diurnal temperature range, spanning 12.5°C to 15.5°C, suggests that these ungulates inhabit areas with signi cant daily temperature uctuations.…”
Section: Relationship Between Environmental Variables and Spatial Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mean annual temperature in the habitats of the two studied ungulates was below − 1.0°C, indicating a strong correlation with suitable habitats at higher altitudes. Studies within the Sanjiangyuan National Park have shown that the habitats of six ungulate species are typically above 4,300 meters, where the mean annual temperature falls below − 3.0°C 19 . The mean diurnal temperature range, spanning 12.5°C to 15.5°C, suggests that these ungulates inhabit areas with signi cant daily temperature uctuations.…”
Section: Relationship Between Environmental Variables and Spatial Dis...mentioning
confidence: 99%
“…Endemic species were mainly considered to be endemic to the Qinghai-Tibet Plateau. China Red List referred to the Red List of China's Vertebrates19 .…”
mentioning
confidence: 99%